Estimated size of the Eastern population of the Lesser White-fronted Goose Anser erythropus revealed from aerial surveys of key moulting sites - Solovyeva, Diana; Rozenfeld, Sonia; Barykina, Daria; Kirtaev, George; Danilova, Valeria; Meng, Fanjuan; Cao, Lei; Lei, Guangchun; Zeng, Qing (Wildfowl, 2024)
The Eastern population of the Lesser White-fronted Goose Anser erythropus (EPLWFG) breeds and moults in Russia and the majority winter in China. Intensive surveys of lakes in the Yangtze River floodplain and in Japan estimated the EPLWFG at 6,600 individuals in 2020 compared to 14,000–19,000 in 2016. Waterfowl are easier to count when concentrated in relatively small areas at key times of the year, and the non-breeding and failed breeding elements of the EPLWFG (an estimated 87% of the population) concentrate at remote moulting sites from early July to mid-August during remigial moult. Locations of GPS-tagged EPLWFG (non-breeding birds and failed breeders), which moulted between 25 June and 17 August, recorded during an earlier study, were plotted on maps of the key moulting region, along the San-Yuryakh and Kyuanekhtyakh Rivers which flow into Omulyakhskaya Bay. An aerial survey undertaken in July 2021 aimed to cover as many locations of the tracked individuals as possible, together with Svyatoy Nos Cape and the New Siberian Islands (where the species was also thought to moult), to count the numbers of geese moulting in these areas. Moulting sites on the delta of the Lena River were also surveyed from the air during the EPLWFG moulting periods in 2019 and 2020. Goose groups were photographed and digitally tagged to GPS coordinates, generating a database which included a date/time stamp to the nearest second, coordinates to the nearest 0.000001 degree, and a picture ID. Photographs were processed using Adobe Photoshop V 21.1.3 software. From detection rates in the survey area, we were able to assess the extent of similar habitat elsewhere in the EPLWFG moulting range, to obtain an estimate of the potential total population size. Moulting EPLWFG were found on Bolshoy Lyakhovaskiy Island in the New Siberian Islands, a new site discovered during this study. A total of 9,373 EPLWFG was counted in moulting flocks at all known and newly discovered moulting sites. The extrapolated estimate for the number of non-breeding and failed breeding birds, on taking the expanded area of suitable habitat into account, was of potentially 24,060 geese. Considering that c. 10% of EPLWFG are successful breeders (i.e. remain on their breeding sites and do not join the moulting flocks), we propose that the overall population size could be as high as 26,733 individuals, excluding offspring of the year.